2019
DOI: 10.1029/2018wr023622
|View full text |Cite
|
Sign up to set email alerts
|

On the Value of ENSO State for Urban Water Supply System Operators: Opportunities, Trade‐Offs, and Challenges

Abstract: The El Niño Southern Oscillation (ENSO) is a major driver of global hydro‐climatic variability, with well‐known effects on floods, droughts, and coupled human‐natural systems. Its impact on urban settlements depends on both level of exposure and preparedness; two factors that are responsible for severe cuts on millions of people in developing countries, where urban water supply relies almost entirely on rainfall‐dependent sources. To understand whether information on the ENSO state could help mitigate the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Forecast reliability, in turn, depends on the available predictive information. An operator might rely on upstream water storage (e.g., soil moisture, snowpack, lake levels) (Shukla and Lettenmaier, 2011), hydrological regime state (Turner and Galelli, 2016), climate indices and teleconnections (Yang et al, 2017;Libisch-Lehner et al, 2019), weather forecasts (Georgakakos et al, 2005;Shukla et al, 2012;Nayak et al, 2018), current river flow rates (Hejazi et al, 2008), knowledge of planned water releases from upstream dams, and perhaps some or all of these in combination (Denaro et al, 2017). This enormous scope for variability in forecast quality and application across dams means there is no obvious way to identify the actual operationalized forecast, or indeed the model used to assimilate it into decision making, for a given system without insight into individual agencies' models and data preferences.…”
Section: Justification For the Concept Of A Horizon Curvementioning
confidence: 99%
“…Forecast reliability, in turn, depends on the available predictive information. An operator might rely on upstream water storage (e.g., soil moisture, snowpack, lake levels) (Shukla and Lettenmaier, 2011), hydrological regime state (Turner and Galelli, 2016), climate indices and teleconnections (Yang et al, 2017;Libisch-Lehner et al, 2019), weather forecasts (Georgakakos et al, 2005;Shukla et al, 2012;Nayak et al, 2018), current river flow rates (Hejazi et al, 2008), knowledge of planned water releases from upstream dams, and perhaps some or all of these in combination (Denaro et al, 2017). This enormous scope for variability in forecast quality and application across dams means there is no obvious way to identify the actual operationalized forecast, or indeed the model used to assimilate it into decision making, for a given system without insight into individual agencies' models and data preferences.…”
Section: Justification For the Concept Of A Horizon Curvementioning
confidence: 99%
“…Therefore, water management in Monsoon Asia should take into account the ocean states. A case study of the Angat River, the Philippines, showed that reservoir operating policies informed by ENSO states are more robust than conventional policies (Libisch-Lehner et al, 2019). Operating policies may be improved further if, say, the PDV is also considered.…”
Section: Implications For Water Managementmentioning
confidence: 99%
“…These river basins are home to 1.7 billion people (Best, 2019). With high population densities, even smaller basins support the livelihood of millions-e.g., Chao Phraya (Thailand): 25 million, Angat (the Philippines): 13 million, and Citarum (Indonesia): 10 million (Nguyen and Galelli, 2018;Libisch-Lehner et al, 2019;D'Arrigo et al, 2011). River discharge, or streamflow, provides water for domestic and industrial uses, irrigation, and hydropower.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, water management in Monsoon Asia should take into account the ocean states. A case study of the Angat River, the Philippines, showed that reservoir operating policies informed by ENSO states are more robust than conventional policies (Libisch- Lehner et al, 2019). Operating policies may be improved further if, say, the PDV is also considered.…”
Section: Implications For Water Managementmentioning
confidence: 99%